2015
DOI: 10.1097/hp.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 222Rn Concentration in an Inhabited Area Adjacent to the Aja Granitic Heights of Hail Province, Saudi Arabia

Abstract: Radon-222 has been measured in groundwater, dwellings, and atmosphere of an inhabited area adjacent to the granitic Aja heights of Hail province, Saudi Arabia. The measurements were carried out in the field using a RAD7 instrument. Twenty-eight water samples, collected from drilled wells scattered in the region, were analyzed. Radon-222 concentration ranged from 2.5-95 kBq m(-3) with an average value of about 30.3 kBq m(-3). The higher values were found in wells drawing water from granitic aquifers. Indoor 222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This factor, together with the indoor measurement condition (indoor air change) contributed to lowering the indoor radon concentration. Another local study [22] indicated an average indoor radon concentration of 54.6 Bq/m 3 . This higher value relates to diff erent factors such as the measurement conditions, where the measurements were carried out in closed chambers (no air change) of town homes located in a high natural background radiation area away from the sea.…”
Section: Discussionmentioning
confidence: 99%
“…This factor, together with the indoor measurement condition (indoor air change) contributed to lowering the indoor radon concentration. Another local study [22] indicated an average indoor radon concentration of 54.6 Bq/m 3 . This higher value relates to diff erent factors such as the measurement conditions, where the measurements were carried out in closed chambers (no air change) of town homes located in a high natural background radiation area away from the sea.…”
Section: Discussionmentioning
confidence: 99%
“…Indoor radon concentrations ranged from 12.0 to 125.6 Bq m −3 . It is anticipated that residents in this area will continuously receive greater radiation doses due to radon gas inhalation and terrestrial radiation [14]. However, although notable, these levels are generally lower compared to the values observed in the Eastern Province, particularly in Qatif City.…”
Section: Introductionmentioning
confidence: 94%
“…21 In Saudi Arabia 222 Rn in outdoor air was measured at 16 sites with values ranging between 6.2 and 13.3 Bq m −3 . 22…”
Section: Instrumentationmentioning
confidence: 99%